Analysis of Segmentation, Targeting and Positioning Strategies in Fraud Risk and Their Impact on Organizational Potential Consequences in Achieving Organizational Goals - Mohammad Firlie Pranata; Unsul Abrar; Amirul Fatoni (PT FORMOSA CENDEKIA GLOBAL, 2022)
Data compiled by Indonesian Corruption Watch shows that during 2016, there were 482 corruption cases with a total state loss of IDR 1.47 trillion (Indonesian Corruption Watch 2017). International Transparency in a 2016 survey showed Indonesia ranked 90th out of 176 countries measured by the level of corruption with a score of 37 (Transparency International 2016). Reform in the field of state finances has been implemented through a package of laws consisting of UUD No. 17 of 2003 concerning State Finance, UUD no. 1 of 2004 concerning the State Treasury and UUD no. 15 of 2004 concerning Examination of State Financial Management and Responsibility. The implementation of the Segmentation, Targeting and Positioning (STP) strategy can be used as a